Double-differential cross sections for ionization of H2O by fast bare O ions: Comparison with continuum-distorted-wave eikonal-initial-state calculations in prior and post forms - Nandi, S. (2013)
O vapor in a static gas condition which allowed us to deduce the absolute value of the cross sections. The single-differential cross sections (SDCS) and the total cross sections have also been obtained. The DDCS as well as the SDCS spectra are compared with the continuum-distorted-wave eikonal-initial-state (CDW-EIS) calculations for both the prior as well as the post forms of the scattering matrix. The initial state is represented within the complete neglect of differential overlap approximation, where the molecular orbitals are expressed in terms of atomic orbitals of the atomic constituents. The overall agreement with the CDW-EIS model is quite good as far as the energy dependence is concerned. The prior form of the model is found to provide a better understanding of the data compared to the post version. In particular, excellent agreement between the theory and experiment has been observed for the angular distribution data at forward angles.